The synthesis of nanosilver and carbamat to control of Anopheles in malaria endemic areas - Raharjo, Mursid; Subagio, Agus; Sulistiyani, Sulistiyani (Intelektual Pustaka Media Utama, 2024)
Malaria is a national and global problem that really needs attention and Indonesia is the second highest country with the highest number of cases 304,607 in 2021. The use of insecticides at inappropriate doses causes resistance to targets. The aim of this study was to analyze the toxicity of silver nanoparticles to adult Anopheles mosquitoes in malaria endemic areas as well as to determine the lethal concentration (LC50) and to project effectiveness in the lifetime. This research is experimental and uses a post-treatment with control design which was carried out in 4 stages from 2019-2022, which includes laboratory scale tests (2019), field laboratory scale tests (2020), ecological endemic area scale tests (2021), and lifetime tests (2022). Calculation of LC50 in nanosilver toxicity 5965 mg/l and Calculation of life time projections produces the formula Y=(-) 0.012Ln(X)+0.6933. Absorption of silver nanoparticles into the bodies of Anopheles sp. occurs through the spiracles and attacks the Ache enzyme in the central nervous system thereby stopping the working system of the mosquito which will then die. Nanosilver is a very effective herbal insecticide used as an effort to control malaria cases in endemic areas with the right dose and method. For life time, a dose of 1500 mg/l nanosilver effectively kills 74% of adult Anopheles sp mosquitoes on day 32 and it is projected that on 1 year the efficacy of nanomaterials still has an efficacy of 62%).